This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The second last row has a slight error in the display
Well, you could just take the square root to each side.
( 5 x − 3 ) 2 = 3 2
5 x − 3 = ± 4 2
5 x = 3 ± 4 2
x = 5 3 ± 4 2
Shouldn't the plus minus sign be in front of 4√2 rather than the whole fraction?
Indeed, a report has pointed that out already. Error in my part; thanks anyway :)
Problem Loading...
Note Loading...
Set Loading...
( 5 x − 3 ) 2 2 5 x 2 − 3 0 x + 9 2 5 x 2 − 3 0 x − 2 3 Using quadratic formula a = 2 5 ; b = 3 0 ; c = − 2 3 x x x x x x x x = 3 2 = 3 2 = 0 = 2 a − b ± b 2 − 4 a c = 2 × 2 5 − ( − 3 0 ) ± ( − 3 0 ) 2 − 4 × 2 5 × − 2 3 = 5 0 3 0 ± 9 0 0 + 2 3 0 0 = 5 0 3 0 ± 3 2 0 0 = 5 0 3 0 ± 1 6 0 0 × 2 = 5 0 3 0 ± 4 0 2 = 5 0 1 0 ( 3 ± 4 2 ) = 5 3 ± 4 2